Gamma distribution parameters estimation from one, two and three weeks precipitation totals in a region of Pelotas, RS - Fonseca, Vera Osorio da; Albuquerque, João Antônio Silva de (Pesquisa Agropecuaria Brasileira, 2014)
The gamma distribution parameters are estimated for precipitation totals of one, two and three weeks, for the region represented by records of the Agroclimatological Post in the Unidade de Execução de Pesquisa de Ámbito Estadual (UEPAE), de Cascata, in Pelotas, Rio Grande do Sul State.